2017
DOI: 10.1016/j.brs.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of the left DLPFC to striatum predicts treatment response of depression to TMS

Abstract: Background Repetitive transcranial magnetic stimulation (TMS) is a non-invasive, safe, and efficacious treatment for depression. TMS has been shown to normalize abnormal functional connectivity of cortico-cortical circuits in depression and baseline functional connectivity of these circuits predicts treatment response. Less is known about the relationship between functional connectivity of frontostriatal circuits and treatment response. Objective/Hypothesis We investigated whether baseline functional connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 64 publications
5
71
0
Order By: Relevance
“…There also is evidence that MDD is characterized by disruptions in other cortico-striatal paths including increased connectivity between the dorsal striatum (DS) and dorsolateral prefrontal cortex (DLPFC) [5], particularly with greater disease severity [17]. Enhanced baseline DS-DLPFC connectivity predicted favorable response to transcranial magnetic stimulation (TMS) [18]. Treatment response was associated with a trend level decrease in DS-DLPFC connectivity, suggesting that reduced DS-DLPFC connectivity correlates with MDD symptom reduction.…”
Section: Introductionmentioning
confidence: 99%
“…There also is evidence that MDD is characterized by disruptions in other cortico-striatal paths including increased connectivity between the dorsal striatum (DS) and dorsolateral prefrontal cortex (DLPFC) [5], particularly with greater disease severity [17]. Enhanced baseline DS-DLPFC connectivity predicted favorable response to transcranial magnetic stimulation (TMS) [18]. Treatment response was associated with a trend level decrease in DS-DLPFC connectivity, suggesting that reduced DS-DLPFC connectivity correlates with MDD symptom reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with dysfunctional connectivity in these networks, and successful rTMS treatment is associated with normalisation of these abnormalities. [11][12][13][14] Current evidence 18 The Canadian authors 18 found that rTMS (both high and low frequency) is suitable as first-line treatment for treatmentresistant MDD, grading the evidence as 'Level I'. The European authors 16 gave rTMS (both high and low frequency) a 'Level A recommendation' and reported 'definite efficacy'.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to optimizing the dosing protocol and testing the durability of the mood improvments, we need to better characterize the subgroup of patients who respond to LFMS. Using functional neuroimaging to understand the circuit abnormalities that are predictive of treatment response has shown great promise for TMS [32][33][34][35][36][37][38]. Mapping these abnormalities in LFMS responders could eventually help match the treatment to depressed patients most likely to benefit and will guide advancements in LFMS coil design to optimize treatment [39,40].…”
Section: Discussionmentioning
confidence: 99%